The Racial Pride of Pagan Virtue: Augustine, Aquinas, and the Amerindians in the Spanish Atlantic Empire - Lantigua, David M. (The Thomist, 2025)
Recent retrievals of Thomas Aquinas on pagan political virtue have generated creative commentary and exegesis for Christian ethics. This article examines the retrieval of pagan virtue discourse among sixteenth-century Spanish humanists and theologians who inhabited the Spanish Atlantic empire and debated the “affair of the Indies.” The historical turn to the New World conquests demonstrates how the racial pride endemic to classical pagan virtue became a matter of dispute pitting an Aristotelian ethic of magnanimity against a Thomistic ethic of charity. The interpretive dispute about pagan virtue between the Spanish humanist Juan Ginés de Sepúlveda and Spanish Dominican theologians concerned whether Augustine’s City of God presented the Roman Empire as a model for heroic virtue or a tyranny of splendid vice. This article considers the distinct political uses of pagan virtue in medieval and early modern political thought with focus on the opposition to the natural racial hierarchy of pagan political virtue by Dominicans Bartolomé de las Casas, Melchor Cano, and Domingo de Soto. Their Thomistic approach with legal and humanist inflections, at once capaciously Aristotelian yet critically Augustinian, further conceptualizes pagan virtue for contemporary Christian ethics and points toward more theological approaches to racial justice and racial solidarity.